Involvement of Mitochondrial Dysfunction in the Inflammatory Response in Human Mesothelial Cells from Peritoneal Dialysis Effluent - Olalla Ramil-Gómez; Mirian López-Pardo; Jennifer Adriana Fernández-Rodríguez; Ana Rodríguez-Carmona; Teresa Pérez-López; Carlos Vaamonde-García; Miguel Pérez-Fontán; María José López-Armada (MDPI AG, 2022)
Recent studies have related mitochondrial impairment with peritoneal membrane damage during peritoneal dialysis (PD) therapy. Here, we assessed the involvement of mitochondrial dysfunction in the inflammatory response in human mesothelial cells, a hallmark in the pathogenesis of PD-related peritoneal membrane damage. Our ex vivo studies showed that IL-1β causes a drop in the mitochondrial membrane potential in cells from peritoneal effluent. Moreover, when mitochondrial damage was induced by inhibitors of mitochondrial function, a low-grade inflammatory response was generated. Interestingly, mitochondrial damage sensitized mesothelial cells, causing a significant increase in the inflammatory response induced by cytokines, in which ROS generation and NF-κB activation appear to be involved, since inflammation was counteracted by both mitoTEMPO (mitochondrial ROS scavenger) and BAY-117085 (NF-κB inhibitor). Furthermore, the natural anti-inflammatory antioxidant resveratrol significantly attenuated the inflammatory response, by reversing the decline in mitochondrial membrane potential and decreasing the expression of IL-8, COX-2 and PGE2 caused by IL-1β. These findings suggest that IL-1β regulates mitochondrial function in mesothelial cells and that mitochondrial dysfunction could induce an inflammatory scenario that sensitizes these cells, causing significant amplification of the inflammatory response induced by cytokines. Resveratrol may represent a promising strategy in controlling the mesothelial inflammatory response to PD.